Chloroplast degradation: one organelle, multiple degradation pathways. (May 2015) - Xie, Qingjun; Michaeli, Simon; Peled-Zehavi, Hadas; Galili, Gad
Abstract : Degradation of chloroplasts is a hallmark of both natural and stress-induced plant senescence. Autophagy and senescence-associated vacuoles are two established cellular pathways for chloroplast degradation. Recently, a third independent pathway for chloroplast degradation was reported. Here we will discuss this new discovery in relation to the other known pathways.